Traditional mineral medicine realgar and Realgar-Indigo naturalis formula potentially exerted therapeutic effects by altering the gut microbiota - Luo, Lu; Li, Chaofeng; Huang, Nanxi; Wang, Qiaochu; Zhang, Zihao; Song, Chen; Yang, Hui; Yuan, Maowen; Xu, Ziwen; Sun, Jialei; Zhang, Zhijie (Frontiers in Microbiology, 2023)
Realgar has a long history of use in traditional medicines. However, the mechanism through which Realgar or Realgar-Indigo Naturalis Formula (RIF) exert therapeutic effects is only partially understood. In this study, 60 feces and 60 ileum samples from rats administered with realgar or RIF were collected to examine the gut microbiota. The results showed that realgar and RIF influenced different microbiota in both feces and ileum. Compared with realgar, RIF at low dosage significantly increased the microbiota diversity. LEfSe and random forest analyses showed that the bacterium Bacteroidales was significantly altered after RIF administration, and it was predicted that these microorganisms contribute to the inorganic arsenic metabolic process. Our results suggest that realgar and RIF may exert their therapeutic effects through influencing microbiota. The low dose of RIF had greater effects on increasing the diversity of microbiota, and Bacteroidales in feces might participate in the inorganic arsenic metabolic process to exert therapeutic effects for realgar.